Psychosocial Rehabilitation - Aruna, G.; Priyadharishini, J. Joy; Manoranjitham, S. (International Journal of Nursing and Medical Investigation, 2024)
Psychosocial rehabilitation (PSR) is a process that facilitates optimum level of functioning among individuals with psychiatric illness and enhances their quality of life. It is a multidimensional approach that involves a team of mental health services and the process begins from the time the person is admitted into a hospital. The goal of the PSR service is to integrate the mentally ill person back into the community and is achieved through various interventions such as symptom management, psychoeducation, vocational rehabilitation, social skills, and life skills training.